Pengaruh Edukasi Melalui Audiovisual Terhadap Pengetahuan Personal Hygiene Saat Mentruasi pada Remaja Putri - Ni Putu Darmayanti; Ni Luh Gede Intan Saraswati; I Gede Juanamasta (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
Lack of knowledge among adolescent girls regarding Personal hygiene during menstruation remains a significant reproductive health problem that contributes to an increased risk of urinary tract infections, skin irritation, and reproductive tract disorders. Limited use of engaging educational methods and suboptimal utilization of modern learning media make health information difficult to understand and remember. This study aimed to analyze the effect of audiovisual-based education on increasing knowledge of Personal hygiene during menstruation among adolescent girls. This study used a quasi-experimental design with a pre-test and post-test with control group approach. The research sample consisted of 62 female students divided into an intervention group of 31 students and a control group of 31 students. The intervention group received health education using an audiovisual video for 30 minutes, while the control group did not receive any intervention. Data were collected using a structured questionnaire to measure knowledge levels before and after the intervention. Data analysis was performed using the Wilcoxon Sign Rank Test to examine within-group differences and the Mann–Whitney U Test to compare differences between groups, with a significance level of ? = 0.05. The results showed a significant increase in knowledge in the intervention group after receiving audiovisual education, as indicated by a shift in knowledge categories from fair and poor to predominantly good, accompanied by a p-value < 0.05. In contrast, the control group did not show significant changes. These findings indicate that audiovisual-based education is effective in improving adolescent girls’ knowledge of Personal hygiene during menstruation. Therefore, the use of audiovisual media is recommended as a reproductive health education strategy in school settings to strengthen sustainable clean and healthy behavior.